Frequency of In-Hospital Diabetic Patients Presented with St Segment Elevation Myocardial Infarction (STEMI) Having Raised Blood Sugar (Medical Forum Monthly, 2021)
Objective: To determine the frequency of inpatient mortality in non-diabetic patients presented with ST segment Elevation Myocardial Infarction (STEMI) having raised blood sugar.Study Design: Descriptive case seriesPlace and Duration of Study: This study was conducted at the Department of Cardiology, PIMS, KIH Islamabad for a period of 6 months from February 2018 to August 2018.Materials and Methods: The total sample was 150 subjects, aged 20 – 60 years, non-diabetic patients with blood sugar level of ≥ 140 mg /dl at presentation, consecutively recruited for the study, having obtained written informed consent.Results: Amongst the participants, 123 (82%) were discharged while only 27 (18%) had expired. Admission hyperglycemia and male sex were significantly associated with mortality.Conclusion: Hyperglycemia on admission is a strong predictor of mortality in patients with STEMI and could be used in the risk stratification of these patients.